Light activation, adaptation, and cell survival functions of the Na+/Ca2+ exchanger CalX. - Wang, T.; Xu, H.; Oberwinkler, J.; Gu, Y.; Hardie, R.C.; Montell, C. (Neuron, 2005)
In sensory neurons, Ca(2+) entry is crucial for both activation and subsequent attenuation of signaling. Influx of Ca(2+) is counterbalanced by Ca(2+) extrusion, and Na(+)/Ca(2+) exchange is the primary mode for rapid Ca(2+) removal during and after sensory stimulation. However, the consequences on sensory signaling resulting from mutations in Na(+)/Ca(2+) exchangers have not been described. Here, we report that mutations in the Drosophila Na(+)/Ca(2+) exchanger calx have a profound effect on activity-dependent survival of photoreceptor cells. Loss of CalX activity resulted in a transient response to light, a dramatic decrease in signal amplification, and unusually rapid adaptation. Conversely, overexpression of CalX had reciprocal effects and greatly suppressed the retinal degeneration caused by constitutive activity of the TRP channel. These results illustrate the critical role of Ca(2+) for proper signaling and provide genetic evidence that Ca(2+) overload is responsible for a form of retinal degeneration resulting from defects in the TRP channel.